Imidocarb dipropionate in the treatment of Anaplasma marginale in cattle: Effects on enzymes of the antioxidant, cholinergic, and adenosinergic systems - Doyle R.L. (2016)
© 2016Anaplasmosis is a worldwide hemolytic disease in cattle caused by a gram-negative obligatory intracellular bacterium, characterized by anemia and jaundice. Among the treatments used for anaplasmosis is a drug called imidocarb dipropionate, also indicated as an immunomodulator agent. However, it causes side effects associated with increased levels of acetylcholine. In view of this, the effects of imidocarb dipropionate on the purinergic system, and antioxidant enzymes in animals naturally infected by Anaplasma marginale were evaluated. Young cattle (n = 22) infected by A. marginale were divided into two groups: the Group A consisted of 11 animals used as controls; and the Group B composed of 11 animals. Imidocarb dipropionate (5 mg/kg) was used subcutaneously to treat both groups (the Group A on day 6 and the Group B on day 0). The treatment reduced acetylcholinesterase (AChE), and adenosine deaminase (ADA) activities, and increased the dismutase superoxide and catalase activities. No changes on lipid peroxidation (TBARS levels) and BChE activities were noticed. These results suggest that imidocarb dipropionate used to treat A. marginale infection in cattle has effect on antioxidant enzymes, and significantly inhibits the enzymatic activities of ADA and AChE.